Peran Literasi Keuangan dan Inklusi Keuangan Terhadap Penggunaan QRIS Di Kota Mataram - Ariani, Ulfatun; Astuti, Widia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study is aimed at determining the influence of Financial Literacy and Financial Inclusion on the Use of Qris in Mataram City. The population in this study is all Qris Users in Mataram City, while the sample of this study is 100 responden QRIS Users. This type of research is an associative research. Data processing in this study uses SPSS 26 version for Windows, where Validity Test, Reality Test, Descriptive Test, Classical Assumption Test, Signification Test (T Test), Determination Coefficient (R) Test, Linear Regression Test, all variables have a positive and significant effect which Financial Literacy and Financial Literacy on the Use of QRIS in Mataram City.